Integrating project-based and experiential learning for lower secondary competencies: A mixed-methods study - Siti Zaenab; Lise Chamisijatin; S. Sukarsono; Diani Fatmawati (Research and Development in Education (RaDEn), 2025)
Project-Based Learning (PjBL) is widely promoted for fostering higher-order thinking, collaboration, and problem-solving, yet its application in lower secondary schools often encounters issues of fluctuating motivation and uneven engagement. This study examined the effectiveness of a PjBL model explicitly structured through Experiential Learning phases in enhancing Grade 8 students’ cognitive, affective, and psychomotor competencies at SMP Muhammadiyah 02 Batu, Indonesia, and explored its implementation across six subjects and students’ perceptions of their learning. Using a mixed-methods Concurrent Triangulation design, 12 teachers joined a professional development workshop before six “model teachers” designed and implemented PjBL units aligned with Kolb’s cycle (experiencing–reflecting–thinking–acting). Data were obtained from teacher knowledge tests, student pre- and post-tests, attitude and skill ratings, student perception and experience questionnaires, and systematic classroom observations, and were analyzed descriptively and thematically. Teacher understanding improved (mean score 8.0 to 9.0/10), and students’ knowledge increased in Science, Social Studies, Mathematics, Indonesian Language, and Arts & Culture, with skills averaging 73–80 and most attitudes rated A or B. Students strongly agreed that PjBL improved collaboration but reported limited consistent reading of project materials. Overall, the integrated model enhanced multiple competence dimensions and was positively received, though stronger support for self-regulated learning and more rigorous future research designs is recommended.